Integrated Energy Recovery and Sugarcane Waste Management - Simiyu, G. M.; Ndung’u, E. W.; Kirimi, K. (Africa Environmental Review Journal, 2017)
Sugar industry produces bagasse, molasses and press mud as wastes. Bagasse has high energy content while press mud is rich in nutrients such as phosphates, calcium and nitrates. Where the boiler efficiency is low, and no proper waste management options are adhered to, excess bagasse is stored in heaps and left to decompose, creating adverse environmental conditions. Briquetting is an option that can effectively consume all wastes from the sugar industry by converting them to a denser form. To increase mechanical strength of the briquettes, binders such as molasses, starch, clay, cement and ash are used. Clay as a binder inhibits combustion and produces more smoke and ash, resulting to low heat energy value, furthermore its excavation from wetlands leads to land degradation. This study endeavored to find ways of enhancing heat energy and nutrients recovery from bagasse and press mud by incorporating the latter as a binder in the making of bagasse briquettes by piston press. Physic-chemical characteristics of the briquettes were tested as per the South African Bureau Standards of household fuel. Calorific value was determined using adiabatic bomb calorimeter procedure. From the trial experiments, the formulation with 52.6% bagasse, 26.3% press mud and 21.05% molasses was found to be the best integrated formulation for energy recovery for sugar industry wastes management.